Fabrications of Low-Cost Poly(methyl methacrylate) Microfluidic Devices for Precise Passive Flow Control - Wattana Kaewtae; Warinthorn Tanasapsakul; Pattaraluck Pattamang; Norabadee Ranron; Witsaroot Sripumkhai; Pimkhuan Hannanta‐anan (My University, 2024)
Microfluidics serve as effective platforms for conducting point-of-care diagnostics and biochemical assays which require precise control over flow rates and incubation times. To enable their uses in resource-limited settings, a pump-free approach is essential for driving fluid flow within the microfluidics. In this study, we introduced cost-effective methodologies for fabricating poly(methyl methacrylate) (PMMA)-based microfluidic devices driven passively by capillary pressure. We explored three fabrication techniques including two-layer CNC micro-milling, two-layer laser engraving, and three-layer laser cutting. Among these methods, three-layer laser cutting proved to be the most reproducible method, yielding devices with consistent channel dimensions and contact angles. Consequently, this fabrication technique enables better control over flow rates within microfluidic systems. Our findings demonstrate the feasibility of fabricating low-cost, pump-free microfluidic devices for precise flow control, with potential applications in disease detection and biomedical research.
Keywords: Microfluidic and Capillary Electrophoresis Applications; Innovative Microfluidic and Catalytic Techniques Innovation; Electrohydrodynamics and Fluid Dynamics